Copper recovery from unground printed circuit board by biogenic ferric at high solid/liquid ratio. (April 2022) - Iglesias-Gonzalez, Nieves; Ramirez, Pablo; Lorenzo-Tallafigo, Juan; Romero-García, Aurora; Mazuelos, Alfonso; Romero, Rafael; Carranza, Francisco
Highlights: Biogenic ferric sulphate leaches Cu from large PCB pieces at high solid–liquid ratio. A bioreactor that regenerates the spent ferric ion assits the leaching. Bioreactor operated continuously without showing inhibition problems. Abstract: In this work, the recovery of Cu from large waste printed circuit board ( PCB) pieces by biogenic ferric sulphate at high solid to liquid ratio was studied. PCB parts were packed in a column and biogenic ferric was constantly recirculated. A high oxidation reduction potential (ORP) decrease was observed in ferric leaching due to ferric ion consumption; this drop caused a slower copper dissolution kinetics. After 25 days, 62.2% of copper was leached from PCBs column. PCBs column was connected to a flooded packed-bed (FPB) bioreactor to study the biological regeneration of ferric ion consumed in chemical reaction. The bioreactor connection enabled working at a constant ORP (700 mV vs. Ag/AgCl) during the whole test time. The improvement of oxidising conditions hugely increased copper dissolution rate, reaching 90% of copper recovery after 25 days. The FPB bioreactor operated continuously without showing inhibition problems and generating a leaching liquor with a high and constant ORP. The novel proposed configuration consists of a chemical reactor, where large PCBs pieces are piled at a high solid load, connected to a FPB bioreactor that regenerates the spent ferric ion enabling the leaching without reagents consumption, is a simple, inexpensive, low energy consumption, eco-friendly and effective system to recover copper from PCBs.